Polarimetric Wide‐Angle Radar Detects Competing Signatures of Ice Fabric and Structural Firn Anisotropy - Falk M. Oraschewski; M. Reza Ershadi; Reinhard Drews (Geophysical Research Letters, 2025)
Abstract Ice is mechanically and dielectrically anisotropic. The degree of anisotropy evolves dynamically as ice crystals align during deformation into macroscopic patterns termed ice fabric. Radar polarimetry is an emerging tool to detect such patterns, particularly using nadir‐looking antenna geometries sensitive to horizontal anisotropy. Although theoretical studies discussed oblique incidence of radio waves to detect vertical anisotropy and relax the assumption of vertical fabric alignment, so far no data were available to test this. Here, we analyze a polarimetric common midpoint survey from Ekström Ice Shelf and develop a framework to invert all relevant ice fabric components. We find that our data not only detect the expected deep ice fabric, but are also significantly impacted by structural anisotropy of near‐surface firn. This has been neglected in previous studies and introduces tradeoffs between both effects in the inversion. It also opens up new possibilities for investigating firn with radar polarimetry.